MENINGKATKAN LITERASI KESEHATAN MENTAL MELALUI PSIKOEDUKASI PADA MAHASISWA BARU PROGRAM STUDI BIMBINGAN KONSELING - Indrawati, Mulyani; Rasido, Ikhlas; Puswiartika, Dhevy; Hasan, Hasan (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
This research investigates the effectiveness of psychoeducational intervention in enhancing mental health literacy among first-year students in the Guidance and Counselling program. The research employed a quasi-experimental with pretest-post test a nonequivalent control group design, using two groups: an experimental group receiving psychoeducation and a control group receiving standard treatment (with 48 students in each group). Mental health literacy scale was assessed using a validated questionnaire administered as both a pretest and a posttest measure. Statistical analysis using the Mann-Whitney U test revealed a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between the experimental and control groups. The experimental group demonstrated substantial improvement, with mean scores increasing from 87.77 (pretest) to 114.13 (posttest), representing a gain of 26.36 points. In contrast, the control group showed minimal improvement, with scores rising from 87.40 to 95.00, a gain of only 7.60 points. These findings provide empirical evidence that psychoeducational intervention significantly enhances mental health literacy among first-year students. ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh psikoedukasi dalam meningkatkan literasi kesehatan mental mahasiswa baru Program Studi Bimbingan dan Konseling. Metode yang digunakan adalah quasi eksperimen dengan pretest-posttest Non equivalent Control Group Design. Sampel terdiri dari dua kelompok: eksperimen dan kontrol, masing-masing terdiri dari 48 mahasiswa Instrumen yang digunakan adalah angket skala literasi kesehatan mental. Perlakuan menggunakan psikoedukasi pada kelompok eksperiman. Hasil analisis statistik menggunakan uji Mann-Whitney menunjukkan nilai signifikansi 0.000 < 0.05, yang berarti terdapat perbedaan signifikan antara kelompok eksperimen dan kontrol. Rata-rata skor posttest kelompok eksperimen meningkat dari 87.77 menjadi 114.13, sedangkan kelompok kontrol dari 87.40 menjadi 95,00. Temuan ini membuktikan bahwa psikoedukasi efektif dalam meningkatkan literasi kesehatan mental mahasiswa baru.